The archive of Grigoris Antoniou - Stylianou-Lambert, Theopisti (My University, 2026)
"The archive of Grigoris Antoniou" is an artwork that was selected to be shown in two international exhibitions - one in Sweden and one in Denmark. Bugs & Metamorphosis: Glitching Photography. Hasselblad Foundation, Sweden. Curated by Louise Wolthers & Nina Mangalanayagam , February 8th - May 4th 2025. “Bugs & Metamorphosis (The Art of Failing 1)” at the Kunsthal Aarhus, Denmark. Curated by Peter Ole Pedersen, June 13th-Dec 31st 2025.